2006
DOI: 10.1107/s160053680602530x
|View full text |Cite
|
Sign up to set email alerts
|

1-(4-Fluorophenyl)-3-(4-methoxyphenyl)prop-2-en-1-one

Abstract: Key indicatorsSingle-crystal X-ray study T = 120 K Mean (C-C) = 0.003 Å R factor = 0.036 wR factor = 0.083 Data-to-parameter ratio = 9.6For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 12 publications
3
14
0
Order By: Relevance
“…Br (1) (1) 1.211(6) C(8)AC (7)AC (4) 127.3(4) C(11)AC (12) 1.355 (7) C(8)AC(7)AH (7) 116.3 C(10)AC (13) 1.353 (7) C(4)AC(7)AH (7) 116.3 C(10)AC (9) 1.458(6) C(3)AC(4)AC (5) 118.9(4) C(9)AC (8) 1.491(6) C(3)AC(4)AC (7) 117.9(4) C(8)AC (7) 1.302 (7) C(5)AC(4)AC (7) 123.2(4) C(8)AH (8) 0.9300 C(6)AC(5)AC(4) 120.6(4) C(7)AC(4) 1.468(5) C(6)AC(5)AH(5) 119.7 C(7)AH (7) 0.9300 C(4)AC(5)AH(5) 119.7 C(4)AC (3) 1.380(6) C(1)AC(6)AC (5) 118.6(4) C(4)AC (5) 1.393(6) C(1)AC(6)AH(6) 120.7 C(5)AC (6) 1.382(6) C(5)AC(6)AH(6) 120.7 C(5)AH (5) 0.9300 C(2)AC(1)AC (6) 122.2(4) C(6)AC (1) 1.376 (7 thermal stability and high second harmonic generation efficiency indicate that it is a promising candidate for NLO applications. Bromine substituted on thiophene ring at one end acts as a strong electron donor and a nitro group on aryl ring at the other end acts as strong electron acceptor thereby enhancing nonlinearity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Br (1) (1) 1.211(6) C(8)AC (7)AC (4) 127.3(4) C(11)AC (12) 1.355 (7) C(8)AC(7)AH (7) 116.3 C(10)AC (13) 1.353 (7) C(4)AC(7)AH (7) 116.3 C(10)AC (9) 1.458(6) C(3)AC(4)AC (5) 118.9(4) C(9)AC (8) 1.491(6) C(3)AC(4)AC (7) 117.9(4) C(8)AC (7) 1.302 (7) C(5)AC(4)AC (7) 123.2(4) C(8)AH (8) 0.9300 C(6)AC(5)AC(4) 120.6(4) C(7)AC(4) 1.468(5) C(6)AC(5)AH(5) 119.7 C(7)AH (7) 0.9300 C(4)AC(5)AH(5) 119.7 C(4)AC (3) 1.380(6) C(1)AC(6)AC (5) 118.6(4) C(4)AC (5) 1.393(6) C(1)AC(6)AH(6) 120.7 C(5)AC (6) 1.382(6) C(5)AC(6)AH(6) 120.7 C(5)AH (5) 0.9300 C(2)AC(1)AC (6) 122.2(4) C(6)AC (1) 1.376 (7 thermal stability and high second harmonic generation efficiency indicate that it is a promising candidate for NLO applications. Bromine substituted on thiophene ring at one end acts as a strong electron donor and a nitro group on aryl ring at the other end acts as strong electron acceptor thereby enhancing nonlinearity.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that extended p conjugated systems with terminal donor-acceptor substituents to exhibit large b values [3,4]. Chalcones are a class of cross conjugated NLO chromophores that is reported to exhibit good SHG efficiency, transparency and are easily crystallizable [5][6][7][8][9][10][11]. In this article, we describe the synthesis, single-crystal growth of 1-(5-bromothiophen-2-yl)-3-(4-nitrophenyl)prop-2-en-1-one (BTNP) and its characterization by IR, proton NMR, DSC and single crystal X-ray diffraction techniques.…”
Section: Introductionmentioning
confidence: 99%
“…A review of antiinfective and anti-inflammatory chalcones (Nowakowska, 2007) and recent advances in therapeutic chalcones have been reported (Ni et al, 2004). The crystal structures of few related fluoro chalcones viz., 3-(3,4-dimethoxyphenyl)-1-(4fluorophenyl)prop-2-en-1-one (Butcher et al, 2006) (Jasinski, et al, 2009), (E)-3-(4fluorophenyl)-1-phenyl-2-propen-1-one (Jing, 2009), 1-(4-fluorophenyl)-3-(4-methoxyphenyl)prop-2-en-1-one (Harrison et al, 2006) and 3-(biphenyl-4-yl)-1-(4-fluorophenyl)prop-2-en-1-one (Sarojini et al, 2007) have been reported. In a continuation of our studies and in view of the importance of fluoro chalcones, we report the synthesis and crystal structure of a new chalcone, C 17 H 16 FNO, (I).…”
Section: S1 Commentmentioning
confidence: 99%
“…It has been shown that extended p systems with terminal donor-acceptor substituents exhibit large b values [3,4]. In these categories, chalcone derivatives are attracting a great deal of attention due to their high NLO coefficients [5][6][7][8][9], and good crystallizability [10][11][12]. As observed in our laboratory [13,14], single crystal structures of two such NLO crystals of chalcone, 1-(4-bromophenyl)-3-(2,4-dichlorophenyl) prop-2-en-1-one (2,4-DiCL-4 0 -bromochalcone), and 3-(2,4-dichlorophenyl)-1-(4-methylphenyl) prop-2-en-1-one (2,4-DiCL-4 0 -methylchalcone), possess a second harmonic generation (SHG) conversion efficiency of about 1.5 and 1.2 times that of urea, respectively.…”
Section: Introductionmentioning
confidence: 99%